Atomistic and Continuum Modeling of Nanocrystalline Materials Deformation Mechanisms and Scale Transition - Capolungo, Laurent (Springer Series in Materials Science, 2009)
Atomistic and Continuum Modeling of Nanocrystalline Materials develops a complete and rigorous state-of-the-art analysis of the modeling of the mechanical behavior of nanocrystalline (NC) materials. Among other key topics the material focuses on the novel techniques used to predict the behavior of nanocrystalline materials. Particular attention is given to recent theoretical and computational frameworks combining atomistic and continuum approaches. Also, the most relevant deformation mechanisms governing the response of nanocrystalline materials are addressed and discussed in correlation with available experimental data. Drawing upon years of practical and academic experience and using numerous examples, authors Mohammed Cherkaoui and Laurent Capolungo cover a wide spectrum of material, including: New modeling techniques and their potential applications and possible extensions, such as molecular dynamics, strain gradient based finite element simulations, and novel micromechanical schemes Novel models describing plastic deformation processes occurring in nanocrystalline materials including grain boundary dislocation emission How to construct and use a molecular dynamics code for practical use in the modeling of NC materials Atomistic and Continuum Modeling of Nanocrystalline Materials is a must have book for researchers as well as graduate students who are either entering these fields for the first time, or those already conducting research in this area and intending to extend their knowledge of nanocrystalline materials.